Multicystic Renal Mass (Archives of Clinical and Medical Case Reports, 2019)
Background: Cystic nephroma It is a benign lesion that can mimic a malignant tumor of the kidney. Case presentation: Here we report a case of multilocular cystic nephroma with unusual localization, largely invading the pyelocaliceal cavities. Conclusions: The importance of its accurate diagnosis is to avoid a radical surgery proposing a partial surgery to preserve a vital organ.